2012
DOI: 10.1080/15548732.2012.683364
|View full text |Cite
|
Sign up to set email alerts
|

Parental Methamphetamine Use and Manufacture: Child and Familial Outcomes

Abstract: The children of methamphetamine (MA) users and manufacturers are at high risk of neglect and abuse and physical harm from exposure to the drug and the chemicals used to produce it. This study is the first to document the epidemiology of children removed from home-based MA labs and their familial outcomes. Analyses are predominantly descriptive for 99 cases of drug-endangered children recorded from 2001–2003 in Los Angeles County. Neglect was substantiated in 93% of the cases; 97% of the cases resulted in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other studies on methamphetamine and child welfare provide further information into this phenomenon. Messina and Jeter (2012) conducted a small study on the child welfare trajectory of children removed from home-based methamphetamine labs in California between 2001 and 2003. Their results indicated that 94% of CPS allegations (most often neglect) were substantiated.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on methamphetamine and child welfare provide further information into this phenomenon. Messina and Jeter (2012) conducted a small study on the child welfare trajectory of children removed from home-based methamphetamine labs in California between 2001 and 2003. Their results indicated that 94% of CPS allegations (most often neglect) were substantiated.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Their results indicated that 94% of CPS allegations (most often neglect) were substantiated. Of the 69 children whose cases received a disposition within the study timeframe, 56 (81%) were returned to the custody of either one or both parents (Messina & Jeter, 2012). Whether the parent who regained custody was a methamphetamine user was not reported, however, and so the impact of parental methamphetamine use on case outcomes in this study remains unknown.…”
Section: Empirical Reviewmentioning
confidence: 99%
“… 21 Findings from the literature suggest that children of methamphetamine users and manufacturers are especially vulnerable to neglect. Messina and Jeter 22 examined 99 cases of children who were removed from home-based methamphetamine labs in Los Angeles County from 2001–2003, and found that 94% of the allegations of child neglect among this sample were substantiated by a Child Protective Services case worker. Children who live in homes where methamphetamine labs exist are not only exposed to the drug itself, but often live in unsanitary environments characterized by the presence of animal feces, ticks, cockroaches, garbage, and drug paraphernalia, 22 24 and are at high risk of ingesting food that is spoiled, rotten, or contaminated with chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous papers (4,30,71,77,114,116,117,(132)(133)(134)(135)(136) highlight issues associated with child welfare, drug use and methamphetamine manufacturing. Children from homes where there is drug abuse and manufacturing frequently live in squalor, neglect and abuse (69,71,73,135,136) where lack of stimulation, poor nutrition, unsanitary conditions and medical problems associated pre-and post-natal exposure to drugs and chemicals (12,69).…”
Section: Confounding Factors For Evaluating Chronic Effects Of Exposurementioning
confidence: 99%